The Effect of Competition Strategies in Influencing Volleyball Performance - Abdullah, Prof. Madya Dr. Mohamad Razali (Springer Science and Business Media Deutschland GmbH, 2021)
In this chapter, we examine the importance of key competitive psychological strategic elements that could be used to identify high- performance players in elite indoor men volleyball tournaments. It is demonstrated that a set of competitional psychological strategic elements , namely self-talk, activation, imagery, emotion control, automaticity, relaxation, goal setting, as well as negative thinking, are essential in determining performance and consequently serve as the indicators that significantly favour high performance in the elite volleyball game. In addition, it was demonstrated that a high classification accuracy in discerning the class, i.e. the performance of the players, could be attained via the k-nearest neighbours classifier. © 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd